2019
DOI: 10.21203/rs.2.10864/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nursing students’ knowledge, attitude, self-efficacy in blended learning of cardiopulmonary resuscitation: a randomized controlled trial

Abstract: Background: Although various forms of online education are on the rise worldwide, effects of such innovative approach are yet to be validated. This study analyzes whether blended learning cardiopulmonary resuscitation (CPR) education that integrates e-learning and face-to-face education is effective in improving nursing students’ knowledge, attitude, and self-efficacy.Methods: A randomized controlled design was used. The participants of this study were 120 nursing students randomly assigned to the intervention… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
(16 reference statements)
1
8
0
2
Order By: Relevance
“…A study by Moon (2019) conducted in South Korea, was identified of blended learning CPR program that integrated videos and face to face lecture. This study's findings have been proven to be effective in increasing the knowledge and attitudes of nursing students regarding CPR after receiving a blended learning video program and face-to-face lectures [18]. An integrative review of blended learning video resources reported that this model is very useful in improving students' knowledge and skills, and preferred more by students because of its flexibility [12].…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…A study by Moon (2019) conducted in South Korea, was identified of blended learning CPR program that integrated videos and face to face lecture. This study's findings have been proven to be effective in increasing the knowledge and attitudes of nursing students regarding CPR after receiving a blended learning video program and face-to-face lectures [18]. An integrative review of blended learning video resources reported that this model is very useful in improving students' knowledge and skills, and preferred more by students because of its flexibility [12].…”
Section: Discussionmentioning
confidence: 74%
“…A total of six studies included in this review are summarized in Table 1. Three of the studies have been conducted in Spain [16,17], two in South Korea [18][19][20], and one was in the Russian Federation [21]. The number of participants included was ranged from 79 IVCN to 213.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nessa perspectiva, as evidências apontam que a simulação clínica contribui para o desenvolvimento de competências psicomotoras, atitudinais e cognitivas, favorecendo a aquisição de conhecimento, habilidades e atitudes referentes ao atendimento a PCR 14,16,17,20 .…”
Section: Discussionunclassified